SUSTAINABLE BUSINESS MODELS FOR CREATIVE STARTUPS IN THE DIGITAL ERA - Judijanto, Loso; Khamaludin, Khamaludin; Mahmudin, Mahmudin; Arisa, Ma’rifani Fitri (Yayasan Adra Karima Hubbi, 2025)
The rise of the digital era has transformed the way businesses operate, especially for startups in the creative industries. As digital technologies reshape market dynamics, the need for sustainable business models that can adapt to rapid changes and ensure long-term success has become crucial. Creative startups, often operating in a highly competitive and fast-evolving environment, face unique challenges in maintaining financial stability while staying innovative. This research aims to explore sustainable business models for creative startups in the digital era, identifying strategies that can drive growth, profitability, and resilience. The study uses a mixed-methods approach, combining qualitative case studies of successful creative startups with quantitative surveys to assess common practices and challenges. Findings reveal that startups employing flexible, customer-centric business models, leveraging digital tools for global reach, and emphasizing continuous innovation are more likely to achieve sustainability. Moreover, the integration of sustainable practices, such as environmentally conscious production and ethical business strategies, has shown to contribute to long-term success. The study concludes that creative startups in the digital era must adopt adaptable, tech-driven business models that prioritize customer engagement and sustainability. By embracing digital transformation, startups can not only survive but thrive in a rapidly changing business landscape.